Matrix Metalloproteinase-2 Knockout and Heterozygote Mice Are Protected from Hydronephrosis and Kidney Fibrosis after Unilateral Ureteral Obstruction. - Maria K Tveitarås; Trude Skogstrand; Sabine Leh; Frank Helle; Bjarne M Iversen; Christos Chatziantoniou; Rolf K Reed; Michael Hultström (PLoS ONE)
Matrix Metalloproteinase-2 (Mmp2) is a collagenase known to be important in the development of renal fibrosis. In unilateral ureteral obstruction (UUO) the obstructed kidney (OK) develops fibrosis, while the contralateral (CL) does not. In this study we investigated the effect of UUO on gene expression, fibrosis and pelvic remodeling in the kidneys of Mmp2 deficient mice (Mmp2-/-), heterozygous animals (Mmp2+/-) and wild-type mice (Mmp2+/+). Sham operated animals served as controls (Cntrl). UUO was prepared under isoflurane anaesthesia, and the animals were sacrificed after one week. UUO caused hydronephrosis, dilation of renal tubules, loss of parenchymal thickness, and fibrosis. Damage was most severe in Mmp2+/+ mice, while both Mmp2-/- and Mmp2+/- groups showed considerably milder hydronephrosis, no tubular necrosis, and less tubular dilation. Picrosirius red quantification of fibrous collagen showed 1.63±0.25% positivity in OK and 0.29±0.11% in CL (p<0.05) of Mmp2+/+, Mmp2-/- OK and Mmp2-/- CL exhibited only 0.49±0.09% and 0.23±0.04% (p<0.05) positivity, respectively. Mmp2+/- OK and Mmp2+/- CL showed 0.43±0.09% and 0.22±0.06% (p<0.05) positivity, respectively. Transcriptomic analysis showed that 26 genes (out of 48 examined) were differentially expressed by ANOVA (p<0.05). 25 genes were upregulated in Mmp2+/+ OK compared to Mmp2+/+ CL: Adamts1, -2, Col1a1, -2, -3a1, -4a1, -5a1, -5a2, Dcn, Fbln1, -5, Fmod, Fn1, Itga2, Loxl1, Mgp, Mmp2, -3, Nid1, Pdgfb, Spp1, Tgfb1, Timp2, Trf, Vim. In Mmp2-/- and Mmp2+/- 18 and 12 genes were expressed differentially between OK and CL, respectively. Only Mmp2 was differentially regulated when comparing Mmp2-/- OK and Mmp2+/- OK. Under stress, it appears that Mmp2+/- OK responds with less Mmp2 upregulation than Mmp2+/+ OK, suggesting that there is a threshold level of Mmp2 necessary for damage and fibrosis to occur. In conclusion, reduced Mmp2 expression during UUO protects mice against hydronephrosis and renal fibrosis.